2014
DOI: 10.1007/s00415-014-7576-4
|View full text |Cite
|
Sign up to set email alerts
|

Successful GPi stimulation in genetic Parkinson’s disease caused by mosaicism of alpha-synuclein gene duplication: first description

Abstract: DBS is an established therapy for advanced PD [1] and has been reported to be efficacious in a few patients with monogenic parkinsonisms such as LRRK2, Parkin, and PINK1 [2][3][4][5][6]. By contrast, knowledge about the outcome of DBS in patients with SNCA mutations is scarce, since only one case has been reported to date [7].We now report the case of a 26-year-old male with Parkinson's disease due to mosaicism of alpha-synuclein duplication, who has successfully undergone GPi-DBS.The patient, who has no famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Five patients were reported in five case reports [46][47][48][49][50] (STN n = 4, GPi n = 1). The motor outcome was favourable for all patients in the short-term but 3/5 patients developed cognitive and/or neuropsychiatric problems a few years after implantation.…”
Section: Sncamentioning
confidence: 99%
“…Five patients were reported in five case reports [46][47][48][49][50] (STN n = 4, GPi n = 1). The motor outcome was favourable for all patients in the short-term but 3/5 patients developed cognitive and/or neuropsychiatric problems a few years after implantation.…”
Section: Sncamentioning
confidence: 99%
“…We are currently employing this technique for the treatment of refractory cases in several movement disorders. 8 In the post -operatory assessment we registered a clear improvement in the dystonic signs. Six months later, there was a 69% mean improvement in the BFMDRS total movement score what meant a P<0.031, (Wilcoxin signed rank test).…”
Section: The Preoperative Neurology Examination Was Performed Withmentioning
confidence: 79%
“…In the few cases of JP reported in the literature, the eligibility for DBS has been greatly based on the phenotype of the patients and on their responsiveness to levodopa. [27][28][29] For instance, the treatment of a 14-year-old patient, with several motor fluctuations, using bilateral DBS in the STN, has been described. Satisfactory results were obtained with this treatment for JP, even though he became refractory to levodopa and had complications in less than 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome was satisfactory, since the symptoms were controlled. 28 Advanced PD patients, with disease onset 40 years before, have benefited from DBS in the STN, with a decrease in dyskinesia and motor fluctuations. 29,30 In spite of the paucity of controlled trials, in some studies it has been reported that DBS can be a good option for the treatment of JP, because it permits the decrease in the dosage of the medication and improves dyskinesia and on/off periods, as observed in the patient of the present case report.…”
Section: Discussionmentioning
confidence: 99%